Program Inovasi Bisnis dan Adaptasi Perilaku Masyarakat Terkait Covid-19 Dalam Kehidupan Sehari-Hari Di Desa Alenangka Kecamatan Sinjai Selatan Kabupaten Sinjai - Hidayat, Taufik (Departemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Community service programs are the practice of science, technology and art (IPTEKS) institutionalized by higher education through direct scientific methods to people who need to succeed in development and human development. Thematic KKN based on Problem Solving to solve problems with certain themes so that student activities are focused on solving certain problems and to achieve certain targets. One of them is the 105th Thematic KKN